Prevalence of Acinetobacter baumannii Multidrug Resistance in University Hospital Environment - Francesco Foglia; Annalisa Ambrosino; Shahab Bashir; Emiliana Finamore; Carla Zannella; Giovanna Donnarumma; Anna De Filippis; Massimiliano Galdiero (Antibiotics)
Background: Acinetobacter baumannii is a significant pathogen and a major contributor to healthcare-associated infections, particularly in intensive care units. Its high potential for developing multiple drug resistance (MDR) makes it a challenging pathogen to manage. This study investigates the prevalence and resistance patterns of MDR A. baumannii isolates over a six-year period at a university hospital in Southern Italy. Objective: The aims of this study are to evaluate recent trends in the prevalence of MDR A. baumannii, analyze resistance patterns, and assess the impact of the antimicrobial diagnostic stewardship program implemented in 2018. Methods: This retrospective cohort study was conducted at the University Hospital of Campania “Luigi Vanvitelli” from 2018 to 2023. A total of 191 A. baumannii isolates from blood, urine, and wound samples were analyzed. Antimicrobial susceptibility testing was performed following EUCAST guidelines. The prevalence of MDR strains was assessed across three periods: pre-pandemic (2018–2019), during the pandemic (2020–2021), and post-pandemic (2022–2023) Results: Among the 191 isolates, 89.5% were classified as MDR. The highest number of isolates occurred in 2020, with blood cultures and urine samples increasing by 40.9% and 62.5%, respectively, while wound isolates decreased by 34.2%. The implementation of antimicrobial diagnostic stewardship programs correlated with a reduction in carbapenem resistance in 2020 and 2022. However, resistance to meropenem and colistin persisted. A 60.4% decline in total isolation from 2020 to 2023 suggests effective infection control measures. Conclusions: MDR A. baumannii remains a significant threat to healthcare. Although there have been slight reductions in resistance following antimicrobial stewardship interventions, persistent resistance to last-line antibiotics underscores the urgent need for alternative treatments, enhanced surveillance, and stricter infection control strategies.